The phenomenon of student evasion in higher education - Simões Rebouças, Willame Anderson (2024)
The aim of this article is to discuss the phenomenon of student evasion in higher education based on national literature. As methodological procedures, we took a qualitative approach and a bibliographic bias. Our bibliographic study was based on the following platforms: Scientific Electronic Library Online and Google Scholar, where searches were limited to the following themes: student evasion; higher education; access and permanence; and higher education. The research emerges from the reflection on the expansion of access to higher education, induced by public policies that have changed the reality of higher education with the opportunity for the lower classes and social minorities to access this level of education, since its elitist origin. However, access is inseparably linked to permanence and its opposite, evasion, which is the focus of our text. We believe that combating dropout is a political, cultural and didactic-pedagogical stance that needs to be built and guided by each institutional reality.